Extraction and characterization of the hydrocolloid from Prosopis flexuosa DC seeds - Ibañez, María Cecilia (2003)
The hydrocolloid present in seeds of the leguminous argentine tree Prosopis flexuosa (“algarrobo dulce”: sweet mesquite) was extracted in different conditions to determine its composition and physico-chemical properties. The content of proteins, carbohydrates, lipids, minerals and moisture were determined both in the seed and the extracted mucilage by standard methods. The total carbohydrate content (including fiber) was 54.1% (w/w) in the seed and ranged from 66.1 to 72.5% (w/w) in the extracts, depending on the extraction procedure. The carbohydrate composition was analyzed by gas chromatography (GC) that revealed the presence of mannose (M) and galactose (G) as major components, with a M/G ratio=2.1. The extracted mucilage was difficult to dissolve in cold water, showing a tendency to form dispersions with pseudoplastic, non-thixotropic behavior. Purification steps (centrifugation, precipitation with isopropylic alcohol) rendered a more soluble product. At concentrations higher than 2%, the mechanical spectra of aqueous solutions revealed a viscoelastic behavior characteristic of systems with entangled macromolecules.